O brincar no processo ensino-aprendizagem da criança - SANTOS, Mairla da Silva (2023)
The present work comes to address the importance of playing in the teaching process child learning in Early Childhood Education for learning. So, this work has as problematic to verify how playfulness can help in the teaching process child learning in early childhood education. Based on the problem raised, it was delimited the general objective which is to analyze the importance of playing with regard to its development and learning in a meaningful way, and has as specific objectives, understand how playfulness can help in the teaching-learning process of child in early childhood education, and also to reflect on the use of playful practices as tool for early childhood education teachers, and finally, to verify how playing make-believe contributes to the child's psychological and social development. To the carrying out the work, a bibliographic research was carried out in order to gather information of authors who have already addressed the topic such as Borba, Corsino, Freire, Góes, Luckesi, Oliveira, etc., and also carried out a field research in order to observe how playing contributes to the teaching-learning process of children in early childhood education. for realization For this research, the ethnographic approach was used, as this method provides the investigator closely monitor the group he is studying. Through this research it became clear the importance of playing in early childhood education with regard to the development in the child's teaching-learning process, also contributing to their physical, social, cultural, affective, emotional and cognitive development.